(untitled) (Tábano, 2020)
Karl Löwith’s Meaning in History presents the emergence of modern philosophy of history as a secularization of medieval theology of history. His thesis holds that modern historical consciousness transposes into the immanent frame a constitutively transcendent element: the Christian history of salvation. In The Legitimacy of the Modern Age Hans Blumenberg impugns Löwith’s theory, by arguing that it works on the erroneous assumption that there would be a substantial content originally possessed by medieval Christianity and only later illegitimately appropriated by modernity. Blumenberg proposes that Löwith’s “transposition” hypothesis must be replaced by his own “reoccupation”: the modern vision of history would have thus taken up the place of Christian eschatology. This paper contends that Blumenberg fails to see that he and his opponent are arguing at different epistemological levels: while Blumenberg’s discussion operates at the level of the efficient causation of history, Löwith’s is focused on the philosophical root of the teleology of the modern idea of progress, which explains this notion as a transposition of the eschaton into a purely immanent telos.